Research Mapping of Fisheries Resource Management in Coastal Areas: A Bibliometric Analysis - Nofirman, Nofirman; Arini, Rani Eka; Muhtadi, Muhamad Ammar (West Science Interdisciplinary Studies, 2024)
This study conducts a comprehensive bibliometric analysis of the literature on government budget efficiency. This bibliometric analysis explores the evolution and integration of themes within fisheries management research from 1959 to 2024. Utilizing VOSviewer for keyword co-occurrence and network visualization, the study identifies dominant themes such as "fishery management system," "conservation," and "sustainability," along with their interconnections and shifts over time. The analysis highlights a multidisciplinary approach, integrating ecological, economic, and technological aspects to address the challenges of sustainable fisheries management. The prominence of terms related to management strategies and environmental conservation reflects a global commitment to sustainable practices. Collaborative patterns among leading researchers and the evolution of research themes underscore the dynamic nature of this field, emphasizing adaptive management strategies that are informed by both socio-economic and ecological dynamics. The findings suggest that the ongoing integration of advanced technologies and interdisciplinary approaches is crucial for developing effective fisheries management practices that can adapt to environmental uncertainties and ensure the sustainability of both marine resources and dependent communities.